A Phase 1 Human Immunodeficiency Virus Vaccine Trial for Cross-Profiling the Kinetics of Serum and Mucosal Antibody Responses to CN54gp140 Modulated by Two Homologous Prime-Boost Vaccine Regimens - Kratochvil, Sven; McKay, Paul F.; Kopycinski, Jakub T.; Bishop, Cynthia; Hayes, Peter John; Muir, Luke; Pinder, Christopher L.; Cizmeci, Deniz; King, Deborah; Aldon, Yoann; Wines, Bruce D.; Hogarth, P. Mark; et al. (Frontiers in Immunology, 2017)
A key aspect to finding an efficacious HIV vaccine is the optimization of vaccine schedules that can mediate the efficient maturation of protective immune responses. In the present study, we investigated the effect of alternate booster regimens on the immune responses to a candidate HIV-1 clade C CN54gp140 envelope protein, which was co-administered with the TLR-4 agonist GLA-AF. Twelve study participants received a common 3-dose intramuscular priming series followed by a final booster at either 6 or 12 months. The two homologous prime-boost regimens were well tolerated and induced CN54gp140-specific responses that were observed in both the systemic and mucosal compartments. Levels of vaccine-induced IgG-subclass antibodies correlated significantly with FcɣR-engagement and both vaccine-regimens were associated with strikingly similar patterns in antibody titer and FcɣR-binding profiles. In both groups, identical changes in the antigen-specific IgG-subclass fingerprint, leading to a decrease in IgG1 and an increase in IgG4 levels, were modulated by booster injections. Here, the dissection of immune profiles further supports the notion that prime-boost strategies are essential for the induction of diverse antigen-specific HIV-1 responses. The results reported here clearly demonstrate that identical responses were effectively and safely induced by both vaccine regimens, indicating that an accelerated 6-month regimen could be employed for the rapid induction of immune responses against CN54gp140 with no apparent impact on the overall quality of the induced immune response. (This study has been registered at ClinicalTrials.gov under registration no. NCT01966900).